2022
DOI: 10.1590/0001-3765202220201909
|View full text |Cite
|
Sign up to set email alerts
|

Hederagenin Exerts Potential Antilipemic Effect via p38MAPK Pathway in Oleic Acid-induced HepG2 cells and in Hyperlipidemic Rats

Abstract: Hederagenin, a natural compound distributed in many medicinal plants, has a variety of pharmacological properties including anti-bacteria, anti-infl ammation, antioxidation, and anti-apoptosis.. The aim of this study was to evaluate the effects of hederagenin on decreasing blood lipid and anti-oxidative stress in oleic acid-induced HepG2 cells and hyperlipidemic rats, and explore underlying mechanisms. In vitro, TG was used as the index to verify the lipid-lowering effect of hederagenin in oleic acid-induced H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It was found that (6aR,11aR)‐9,10‐dimethoxy‐6a,11a‐dihydro‐6H‐benzofurano[3,2‐c]chromen‐3‐ol can act on tyrosine tRNA synthetase and tryptophanyl tRNA synthetase TrpRS to modulate the biosynthesis of aminoacyl‐tRNA, regulate DNA damage and apoptosis (Chen et al., 2018). Hederagenin has a variety of pharmacological effects such as reversing hyperlipidemia, anti‐depression, anti‐lipid peroxidation, liver protection, and anti‐inflammation (Choi et al., 2001; Gülçin et al., 2006; Lin et al., 2021; Shen et al., 2023; Yamahara et al., 1979; Yang et al., 2022). Notably, hederagenin can play a protective role in blood vessel wall by modulating lipid metabolism disorder and lipid deposition (Lu et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that (6aR,11aR)‐9,10‐dimethoxy‐6a,11a‐dihydro‐6H‐benzofurano[3,2‐c]chromen‐3‐ol can act on tyrosine tRNA synthetase and tryptophanyl tRNA synthetase TrpRS to modulate the biosynthesis of aminoacyl‐tRNA, regulate DNA damage and apoptosis (Chen et al., 2018). Hederagenin has a variety of pharmacological effects such as reversing hyperlipidemia, anti‐depression, anti‐lipid peroxidation, liver protection, and anti‐inflammation (Choi et al., 2001; Gülçin et al., 2006; Lin et al., 2021; Shen et al., 2023; Yamahara et al., 1979; Yang et al., 2022). Notably, hederagenin can play a protective role in blood vessel wall by modulating lipid metabolism disorder and lipid deposition (Lu et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…According to the drug-active ingredient-target network analysis, quercetin, kaempferol, beta-sitosterol, diosgenin, kadsurenone, hederagenin, sitosterol and stigmasterol may play a main role in the treatment of hypothyroidism.Modern pharmacological studies have shown that [17] quercetin has anti-inflammatory, antioxidant, immunomodulatory and anti-tumor effects.Studies have shown [18] that quercetin can activate TPO of rats, make them produce well-differentiated metabolite 3,5-L-diiodotyrosine, and promote the expression of TPO and the production of L-thyroxine.Quercetin also has certain regulatory effect on inflammatory release and apoptosis of epithelial cells [19] ;Stigmasterol has the effects of anti-inflammation, lowering cholesterol and improving memory [20][21][22] ;β-sitosterol can inhibit apoptosis of granulosa cells, which is related to regulation of endocrine hormone, neuroprotection and anti-inflammation [21][22][23][24] ;Kaempferol has antioxidant, anti-inflammatory, heart protection, nerve protection, anti-diabetes, anti-osteoporosis, anti-anxiety effects [25].Diosgenin can improve cardiac function and reduce inflammatory reaction, which is related to cell apoptosis and endocrine hormone regulation process [26][27].Kadsurenone inhibits inflammatory mediators [28].Hederagenin is neuroprotective, anti-inflammatory, anti-apoptotic, and lipid-lowering [29][30].Conclusion: These components may be the core components of Liuwei Dihuang pill in the treatment of hypothyroidism, and have certain clinical research value.…”
Section: Discussionmentioning
confidence: 99%
“…Similar antilipemic effects were also observed for hederagenin. This pentacyclic triterpene exerts its potential through the p38MAPK pathway in oleic acid-induced HepG2 cells and in hyperlipidemic Sprague-Dawley rats [168].…”
Section: Anti-diabetic Activitymentioning
confidence: 97%